Wiring Diagram For The Ventilation Panel : Gambar Wiring Pada Panel Ventilasi - Rochman, Achmad Fatchur; Wisaksono, Arief (Procedia of Engineering and Life Science, 2024)
Wiring diagrams are an essential tool in the maintenance and repair of electrical systems, enabling quick identification of the source of the problem. Knowledge of electrical component symbols and their functions is important in reading wiring diagrams. Ventilation systems play a crucial role in closed environments such as chicken coops, maintaining air circulation and appropriate temperatures. Settings can be made automatically via the climate controller and control panel. Therefore, a basic understanding of the use of these devices is important for breeders. The research method used is descriptive qualitative with data collection in the field, especially at CV. Bintang Pratama Teknik, to study ventilation panels from wiring drawing in AutoCAD to assembly. The research results include an understanding of components such as electrical panels, AutoCAD, MCB, TOR, contractors, busbars, duct cables, and terminals. Drawing components using AutoCAD allows a better understanding of their design and functionality.